Seasonal carrion Diptera and Coleoptera communities from Lisbon (Portugal) and the utility of forensic entomology in legal medicine - Castro, Catarina Barros de Prado e 1979- (2011)
Tese de doutoramento, Biologia (Ecologia), Universidade de Lisboa, Faculdade de Ciências, 2011